Vortex matter phase diagram in HgBa2CuO4+delta single crystals - Stamopoulos, D.; Pissas, M. (PHYSICA B-CONDENSED MATTER, 2000)
We used local AC-susceptibility and global DC magnetization measurements to determine the magnetic phase diagram of two HgBa2CuO4+delta single crystals with T-c = 95 and 89.9 K, respectively. The corresponding lines for the more anisotropic crystal (T-c = 89.9 K, crystal A) lie lower than those of the nearly optimally doped crystal (T-c = 95 K, crystal B). The irreversibility line (IL) decreases exponentially in the temperature range 20 less than or equal to T less than or equal to T*. At T* = 82 and 88 K the IL change slope and varies with a power law up to the T-c. Certain features in these measurements are also discussed. (C) 2000 Elsevier Science B.V. All rights reserved.